The Style and Timbre of English Speech and Literature - Konurbaev, Marklen E.; SpringerLink (Online service) (London : Palgrave Macmillan UK : Imprint: Palgrave Macmillan, 2016)
The book introduces the reader into the world of mental perception of literary contents. Based on the research in modern semantics, functional stylistics and cognitive phonetics, it explores the way linguistic elements of a literary work cause readers to form a single perception shape identified as a cultural, literary or social stereotype.
Keywords: Linguistics; Literature; Phonology; English language; Pragmatics; Language and languages -- Style; Literacy; Linguistics; English; Stylistics; Literature, general; Pragmatics; Phonology; Literacy; Electronic books